High-stakes testing and English teachers' role as materials developers: Insights from vocational high schools - Elsa Ananda; Ashadi Ashadi (Studies in English Language and Education, 2021)
The implementation of the National Examination (NE) in Indonesia in elementary to high schools is considered as high-stakes testing and affects the teachers’ practice particularly in vocational settings. As material developers, English teachers in Vocational High Schools (VHS) are demanded to develop appropriate and suitable materials to meet the students’ specific needs. The incompatibility of the NE materials prescribed by the government and the vocational students’ needs put the teachers in a dilemma. The teachers should deal with the pressure of the NE and their roles as materials developers. This article tries to reveal how high-stakes testing impacts their roles as material developers particularly in the absence of specifically prescribed materials for VHS students. A case study design was used in this research with 31 participants of English teachers from nine state VHS in Pontianak, Indonesia. Data were collected through questionnaires and interviews. The result revealed that the role of teachers as materials developers somehow becomes diminishing because of the presence of the NE as high-stakes testing in the learning process, especially in VHS. This condition is detrimental to the teachers’ professional development since their roles as materials developers are limited and even under-developed. With the cancellation of NE by the end of this year, it is expected that the teachers are able to play their roles as materials developers and conduct evaluations based on the students’ specific expertise.